Aquariibacter albus gen. nov., sp. nov., a new member of the order Burkholderiales, isolated from a freshwater aquarium. Issue 10 (1st October 2021) - Cui, Yingshun; Park, Chan-Yeong; Kim, Song-Yeon; Wong, Shu-Kuan; Lim, An Suk; Oh, Hee-Mock; Chun, Seong-Jun; Ahn, Chi-Yong
Abstract : A novel bacterium, strain SJAQ100 T, was isolated from a freshwater aquarium and was characterized taxonomically and phylogenetically. Strain SJAQ100 T was a Gram-stain-negative, aerobic, rod-shaped and non-motile bacterium. The strain grew optimally with 0 % NaCl and at 25–37 °C on Reasoner's 2A agar. Phylogenetic analysis based on the 16S rRNA gene sequences revealed that the strain SJAQ100 T clustered with members of Burkholderiales incertae sedis in the order Burkholderiales, but sequence similarities to known species were less than 96.5 %. The genomic DNA G+C content of strain SJAQ100 T was 71.2 mol%. Genomic comparisons of strain SJAQ100 T with species in the order Burkholderiales were made using the Genome-to-Genome Distance Calculator, average nucleotide identity and average amino acid identity analyses (values indicated ≤22.1, ≤78.1, and ≤68.1 % respectively). Strain SJAQ100 T contained C16 : 0 and C16 : 1 ω 7 c /C16 : 1 ω 6 c as major fatty acids and Q-8 as the major quinone. The major polyamines were putrescine and cadaverine. Strain SJAQ100 T contained phosphatidylethanolamine and diphosphatidylglycerol as major polar lipids. Based on the genotypic, chemotaxonomic and phenotypic results, strain SJAQ100 T represents a novel genus and species, Aquariibacter albus gen. nov., sp. nov., which belongs to order Burkholderiales and the class Betaproteobacteria . The type strain is SJAQ100 T (=KCTC 72203 T =CGMCC 1.18869 T =MCC 4385 T ).